Análisis del sexismo implícito en el programa televisivo Mi Recinto - Dávila Barrera, María Emilia (2016)
This investigation focuses in the analysis of sexism content found on Mi Recinto, a comedy that aired for 13 years and was transmitted by national television, reaching the highest levels of audience. According to CIESPAL and the Latin American Observatory of Communication, such ratings, catapulted the program as one of the most seen shows in Ecuadorian television. The analysis explores the discursive practices of sexism in the program, given that television is an intrinsic part in the life of human beings, which merits an understanding of the topic. The analysis also goes into Article 8 of the Ley Orgánica de Comunicación (LOC), which pretends to transmit content, with a propensity towards quality and transmission of values. The methodology applied in this investigation was an analysis on the content of the transmitted programs to determine the factors that influence on sexism constructions found therein. At the same time, an analysis of the audience was conducted through a focus group of 8 with the purpose of understanding their views on the social and gender constructs exemplified in the content of the program. The investigation also determined the social impact generated by the program. As a result of this investigation it was established that the content of Mi Recinto, did not comply with the articles established by the Ley Orgánica de Comunicación, with its characters based on social stereotypes. It was also determined that sexism is an important social factor that contributes to gender constructions.